Sudden cardiac death in isolated right ventricular hypertrabeculation/noncompaction cardiomyopathy. Issue 4 (12th September 2017) - Bekheit, Soad; Karam, Boutros; Daneshvar, Farshid; Zaidan, Julie; Tabet, Rabih; Spagnola, Jonathan; Lafferty, James
Abstract: Hypertrabeculation/noncompaction of the myocardium is a rare disorder that involves most commonly the left ventricle of the heart and it has been recognized as a distinct cardiomyopathy by the World Health Organization. However, it is extremely rare for this condition to involve exclusively the right ventricle. We report the cases of three patients who presented with ventricular tachyarrhythmia and sudden cardiac death. They were found to have isolated right ventricular hypertrabeculation/noncompaction on echocardiography. This supports the hypothesis that this condition is highly arrhythmogenic and is associated with high mortality similarly to the left ventricular hypertrabeculation/noncompaction cardiomyopathy.